PENGARUH GAYA KEPEMIMPINAN TERHADAP ETOS KERJA KARYAWAN DI PT. INATEL NUSANTARA - A.A. Istri Ngurah Dyah Prami; Ni Kadek Ria Jestilia (Majalah Ilmiah Widyacakra, 2020)
ABSTRACTThe tittle research is The Influence of Leadership Style On Employee Work Ethic at PT. InatelNusantara. Leadership is the most important factor to influencing the achievement oforganization. If in an organization there are good and mature of leadership style, so theemployee work ethic may increase and at the end it will accelerate directly to the process ofachieving the company goals. This research aimed to analyze the influence of the LeadershipStyle On Employee Work Ethic at PT. Inatel Nusantara.. The sample of this research is 60respondents at PT. Inatel Nusantara. The Data sources used in this research are primary andsecondary data. Data is analyzed using path analysis that is assisted with SPSS for Windowsversion 22. Data collection method in this research using interview method, by means ofquestionnaires. The analytical technique used is simple linier regression analysis. Results ofstatistical analysis known that the leadership style influenced on employee work ethic at PT.Inatel Nusantara is 50,1%, based on hypothesis testing with the t test result, it can beconcluded that the leadership style variable (X) significantly influence on employee workethic variable (Y) with value of t-test is 7,637 and sig. 0,000.